2022
DOI: 10.1002/admi.202201604
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field‐Induced Synthesis of One‐Dimensional Nickel Nanowires for Enhanced Microwave Absorption

Abstract: One‐dimensional magnetic nanowires have become one of the ideal candidates for microwave absorption (MA) due to their excellent mechanical properties, large aspect ratio, and excellent electron transport properties. Here, we introduce the synthesis of polyvinylpyrrolidone (PVP)‐directed nickel nanowires (PNNWs) by an externally magnetically induced solvothermal method, and the morphology and properties of PNNWs exhibit a magnetic field‐strength‐dependent relationship. The 9T‐PNNW synthesized at 9 T magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Therefore, the triplet/singlet ratio of the radicals, produced in the reduction process, might be modified remarkably [34], which could negatively influence the amount and stability of the resultant dianions and thus be correlated to deteriorated magnetic properties of the PDI magnets. The situation is different from the cases of the synthesis of the nanomaterials under HML [25,26], in which the formation of the product phases with a higher magnetic order is facilitated due to the lowering of magnetic energy upon the generation of these products under the magnetic field. On the other hand, the assembly and growth of the radical PDI aggregates could also be modulated via the solution cast of the dianion solution under HMF to study the MFE on the structure and magnetic properties of the PDI magnets.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, the triplet/singlet ratio of the radicals, produced in the reduction process, might be modified remarkably [34], which could negatively influence the amount and stability of the resultant dianions and thus be correlated to deteriorated magnetic properties of the PDI magnets. The situation is different from the cases of the synthesis of the nanomaterials under HML [25,26], in which the formation of the product phases with a higher magnetic order is facilitated due to the lowering of magnetic energy upon the generation of these products under the magnetic field. On the other hand, the assembly and growth of the radical PDI aggregates could also be modulated via the solution cast of the dianion solution under HMF to study the MFE on the structure and magnetic properties of the PDI magnets.…”
Section: Resultsmentioning
confidence: 81%
“…They found that the formation of the metallic 1T-MoS 2 phase is facilitated under a high magnetic field (HMF) due to the higher magnetic susceptibility of 1T-MoS 2 than diamagnetic 2H-MoS 2 [25]. Qian et al have synthesized the PVP-directed nickel nanowires via a magnetically assisted hydrothermal method, which also exhibited enhanced magnetization and excellent microwave absorption performance [26]. Furthermore, our group has achieved a large area highly oriented film structure of several semiconducting polymers by solution-phase deposition under a field of 9T [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing EWA studies related to Ni nanowires seldom show superior properties due to the inferior impedance matching, which originates from the high conductivity caused by the easy escaping of electrons and the linear structure. As reported, the current methods for fabrication of Ni nanowires are magnetic field-induced, electrodeposition, template-assisted, and solvothermal reactions. Among them, the solvothermal reaction has various advantages, such as cost-free, moderate reaction conditions, even size, and a large length-to-diameter ratio, prompting the development of Ni nanowire-related absorbing materials.…”
Section: Introductionmentioning
confidence: 99%